2016
DOI: 10.1155/2016/2932697
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Antibiotics following Simple Exodontia

Abstract: Introduction. The aim of our study is to assess the need for postoperative antibiotics following simple exodontia and determine its role in minimizing patient discomfort and postoperative complications. Material and Methods. All the patients undergoing simple extractions were grouped into two categories: Group 1, patients receiving antibiotics, and Group 2, patients receiving no antibiotics. Patients were recalled on the sixth day to assess postoperative complications. On recall, patients were evaluated for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Most of the times the body's host response is more than sufficient to counter the level of bacteremia anticipated. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the times the body's host response is more than sufficient to counter the level of bacteremia anticipated. 19…”
Section: Discussionmentioning
confidence: 99%
“…Most of the times the body's host response is more than sufficient to counter the level of bacteremia anticipated. 19 On the contrary, only 24.7% of the dentists were aware of the latest AAPD guidelines (►Table 3) and majority of the…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that antibiotic prescription is not necessary in healthy patients as long as strict aseptic and antiseptic management is performed. [56][57][58] A lower percentage of dentists erroneously prescribed antibiotics during endodontic treatments without systemic symptoms (18.7 percent), periodontal treatment without surgery (11.7 percent), gingivitis (13.9 percent), anesthetic complications (4.9 percent), and pain (3.6 percent). Abbot 59 interviewed US dentists and endodontists to learn the prescription of antibiotics for different pulpal and periapical conditions and found that these professionals used Chi-square test to compare the awareness, attitudes, and intention to practice levels among dentists in the seven cities.…”
Section: Discussionmentioning
confidence: 99%
“…14 Another study conducted by Lodi et al in 2012 showed that the administration of antibiotics with inappropriate indications can cause adverse effects such as vomiting, diarrhea, abdominal pain, secondary infections, allergic reactions, and bacterial resistance. 3,[15][16][17] One of the effects of the use of antibiotics that has a big influence is bacterial resistance to antibiotics. Bacterial resistance to antibiotics is a condition in which bacteria can survive after being given antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%